Abbott Elementary. The complete fourth season [videorecording (DVD)] - Brunson, Quinta (Warner Bros., 2026)
Season Four of Abbott Elementary begins with the teachers returning from summer vacation to find that the neighboring construction site of a new golf course is causing issues at Abbott, forcing the teachers to find creative solutions. Plus, an HR representative visits the school. Following their kiss, Janine and Gregory's relationship status is revealed.